PENANGANAN KEAMANAN WILAYAH PERBATASAN: STUDI KASUS PENYELUNDUPAN TRANSIT MIGRAN DARI TIMUR TENGAH KE AUSTRALIA MELALUI INDONESIA 2010-2013 - Yusrina, Nietya Amalia; Utomo, Tri Cahyo; Pattipeilohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Over the past decades, the world has witnessed the increasingnumber of migrants originating from the Middle East due to theeconomic and political instabilities they face at home. Australia hasbeen one of the most popular destinations the migrants tend tomigrate to, as the country is perceived to be offering manyopportunities and promosing living envinronments. Before arrivingin Australia however, it is common for many migrants to make atransit in Indonesia either under legal or illegal means. The illegalones have particularly been problematic for Indonesian Governmentas they have presented the country with a number of unprecedentedsocial, economic, and political consequences. In this research, byusing the qualitative method, the writer aplies the theory ofConstructivism by Martha Finnemore to analyze the factors thatmake the migrants incline to transit in Indonesia unlawfully, eventhough many legal efforts to tackle this issues have been placed bythe Indonesian National Police. The result of this research showsthat Indonesia's geography, legal, economic and socio-culturalconditions are among many factors that could be held responsiblefor the case. As such, the Indonesian National Police have donepreemptive, preventive and repressive efforts to overcome thesefactors.